2021
DOI: 10.1002/ange.202101628
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Kinetic and Spectroscopic Signatures of Copper Sites for Direct Oxidation of Methane to Methanol

Abstract: Copper‐exchanged zeolites of different topologies possess high activity in the direct conversion of methane to methanol via the chemical looping approach. Despite a large number of studies, identification of the active sites, and especially their intrinsic kinetic characteristics remain incomplete and ambiguous. In the present work, we collate the kinetic behavior of different copper species with their spectroscopic identities and track the evolution of various copper motifs during the reaction. Using time‐res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(8 citation statements)
references
References 87 publications
(154 reference statements)
0
8
0
Order By: Relevance
“…42 Despite this, the E a,app found here, compared to that computed by Heyer et al using a cluster model (19.3 kcal mol −1 ), 42 is closer to the reported experimental value (7.9 ± 2.3 kcal mol −1 ). 23 Comparing the geometries of TS Ho and TS He (Fig. S2 †), we found them similar except that TS He also involves a C⋯Cu interaction in addition to the C⋯H⋯OH interactions.…”
Section: Structure and Stability Of Cuoh-mormentioning
confidence: 68%
See 4 more Smart Citations
“…42 Despite this, the E a,app found here, compared to that computed by Heyer et al using a cluster model (19.3 kcal mol −1 ), 42 is closer to the reported experimental value (7.9 ± 2.3 kcal mol −1 ). 23 Comparing the geometries of TS Ho and TS He (Fig. S2 †), we found them similar except that TS He also involves a C⋯Cu interaction in addition to the C⋯H⋯OH interactions.…”
Section: Structure and Stability Of Cuoh-mormentioning
confidence: 68%
“…In addition, the authors concluded that two kinds of Cu monomers (i.e., Cu 2+ and CuOH + ) coexist in Cu-MOR, but only the latter is CH 4reactive. 23 Whether the Cu 2+ site acts only as a spectator (redox-inert) 38,39 or also plays a primary 40 42 However, in contrast to the findings by Sushkevich et al, 23 this CuOH monomer has been reported to be less reactive than the Cu 2 O dimer. 42 Another example of Cu monomer, i.e., Cu single atom catalyst on different supports, [43][44][45] was also reported to be active for the CH 4 oxidation to CH 3 OH.…”
Section: Introductionmentioning
confidence: 88%
See 3 more Smart Citations